Hubungan Klasifikasi Hipertensi Terhadap Penurunan Fungsi Kognitif Pasien Hipertensi di Puskesmas Pekauman Kota Banjarmasin: The Relationship of Hypertension Classification to Decreasing Cognitive Function of Hypertension Patients at Pekauman Health Center, Banjarmasin City - I Gede Deriana; Eirene E.M. Gaghauna; Bagus Rahmat Santoso (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Cognitive function is a person's ability to think, recall and pay attention, including in the learning process. Decrease and disturbance of cognitive function when there is a decrease and disturbance of the noble functions of the brain such as concentration, memory, language, intellectual functions such as counting. An increase in blood pressure that is not controlled can cause a reduction in blood flow to the brain, causing brain performance to be disrupted, with one of the symptoms being a decrease in cognitive function. Of course, decreased cognitive function in hypertensive patients can directly affect the quality of life of sufferers, where currently decreased cognitive function is the cause of a person's inability to carry out normal activities. Hypertension is an abnormal increase in blood pressure, both systolic blood pressure and diastolic blood pressure. In general, a person is said to have hypertension if his blood pressure is > 140/90 mmHg (normally 120/80 mmHg). To determine the relationship between hypertension classification and cognitive function decline. Quantitative study with the type of analytic observation with a cross-sectional approach. Using purposive sampling method, the number of samples is 71 people. The analytical test used was chi-square, the research instrument was the MMSE questionnaire and a digital sphygmomanometer. It turns out that many respondents experienced decreased cognitive function, so they need to maintain a healthy lifestyle and blood pressure to remain stable so that cognitive function decline does not occur.